Saving in Latin America and the Caribbean : Performance and Policies - Grigoli, Francesco (IMF Working Papers; Working Paper ;, 2015)
This paper analyzes saving patterns and determinants in Latin America and the Caribbean (LAC), including key policy variables and regimes. The review of previous empirical studies on LAC saving reveals contradictions and omissions. This paper presents empirical results of an extensive search of determinants of private and public saving rates, adding previously neglected variables (including different measures of key external prices and macroeconomic policy regimes), in linear form and in interactions with other saving determinants. It analyzes statistical differences in saving determinants between LAC and the rest of the world in a nested econometric framework, and discusses differences across three country subgroups within LAC. The results highlight commonalities and differences in saving behavior between LAC and other world regions, as well as within LAC, identifying the role of key policy variables and regimes.